Metamorphic history of the South Tibetan Detachment System, Mt. Everest region, revealed by RSCM thermometry and phase equilibria modelling - Cottle, J; Waters, D; Riley, D; Beyssac, O; Jessup, M (2011)
This study combines microstructural observations with Raman spectroscopy on carbonaceous material (RSCM), phase equilibria modelling and U-Pb dating of titanite to delineate the metamorphic history of a well-exposed section through the South Tibetan Detachment System (STDS) in the Dzakaa Chu valley of Southern Tibet. In the hanging wall of the STDS, undeformed Tibetan Sedimentary Series rocks consistently record peak metamorphic temperatures of ~340°C. Temperatures increase down-section, reaching ~650°C at the base of the shear zone, defining an apparent metamorphic field gradient of ~310°Ckm across the entire structure. U-Th-Pb geochronological data indicate that metamorphism and deformation at high temperatures occurred over a protracted period from at least 20 to 13Ma. Deformation within this 1-km-thick zone of distributed top-down-to-the-northeast ductile shear included a strong component of vertical shortening and was responsible for significant condensing of palaeo-isotherms along the upper margin of the Greater Himalayan Series (GHS). We interpret the preservation of such a high metamorphic gradient to be the result of a progressive up-section migration in the locus of deformation within the zone. This segment of the STDS provides a detailed thermal and kinematic record of the exhumation of footwall GHS rocks from beneath the southern margin of the Tibetan plateau. © 2011 Blackwell Publishing Ltd.